Passive Q‐switched operation of Tm:YAP laser with a TaTe2 saturable absorber. Issue 5 (12th December 2022) - He, Xin; Qi, Tianqi; Gao, Qiong; Yang, Wenlong; Yu, Shuang
Abstract: In this paper, a Tm:YAP all‐solid‐state continuous wave (CW) and passive Q‐switched (PQS) laser were experimentally proved by using a TaTe2 ‐based saturable absorber (SA) for the first time. Under the CW mode, the maximum output power was 4.99 W and the slope efficiency was 29.8%. Based on TaTe2 SA, the shortest pulse width of 585 ns at the central wavelength of 1987.9 nm was obtained with the pump power of 17.73 W, corresponding to single‐pulse energy of 9.7 µJ and an average output power of 1.86 W. Also, a pulse repetition frequency of 202.4 kHz was achieved in the PQS Tm:YAP laser when the pump power was 13.51 W.